Decision Support Systems Employee Discipline Identification Using The Simple Multi Attribute Rating Technique (SMART) Method - Rizer Fahlepi (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2020)
Discipline is a very important aspect to support the quality of these human resources. If there are insufficient or undisciplined resources, it will affect the quality of human resources. In its implementation the process of evaluating employee discipline is still done manually so it takes a long time. For this reason, a decision support system is needed to identify the level of discipline of staff and employees at STIKes and STMIK Hang Tuah Pekanbaru. The method used to develop this DSS is Simple Multi Attribute Rating Technique (SMART) with 6 attributes, namely performance, warning letters, absenteeism, discipline, complience to regulations, and compliance to superior’s order. The final result are divided into 3 categories, namely Very Good, Enough, Do Coaching. From the application of this method, it was found that 120 people got Very Good evaluation results, 11 people got Enough results, and 2 people got the results of Do Coaching. Decision support system with SMART method can identify the level of discipline of staff and, to later be given guidance to staff who get evaluation results. Do Coaching to become more disciplined and improve the quality of human resources in STIKes and STMIK Hang Tuah Pekanbaru